The complete mitochondrial genome of Propsilocerus akamusi (Diptera, Chironomidae) - Zhang, Qingji (Mitochondrial DNA B Resour, 2019)
Propsilocerus akamusi is one of the most important genera of Chironomidae. However, the systemically classification and taxonomic studies have so far been limited. In this study, we report the complete mitochondrial genome sequence of P. akamusi. The mitogenome has 15,632 base pairs (77.58% A + T content) and made up of total of 37 genes (13 protein-coding, 22 transfer RNAs, and 2 ribosomal RNAs). This study will provide useful genetic information for future phylogenetic and taxonomic classification of Chironomidae.